CHORIORETINITIS SCLOPETARIA: OCULAR TRAUMA DUE TO FIREARM PELLETS - Singh, Ravdeep; Aggarwal, Akash D (Journal of Forensic Medicine and Toxicology, 2018)
Penetrating eye injuries are common preventable causes of visual impairment and visual loss. Many eye injuries are related to particular occupations and certain cultures.Chorioretinitis sclopetaria is a rare ophthalmic finding in trauma. We report of a 22-year-old male patient, who suffered a gunshot wound that passed behind his eyes and developed scleral necrosis and uveal fibrosis from sclopetaria induced by indirect trauma.